Analysis of Indonesian Tea Export Competitiveness on the International Market - Ulfah Muflihah; Abdul Mutolib; Candra Nuraini (East Asian Journal of Multidisciplinary Research, 2023)
This research aims to determine the competitiveness of tea in the international market. The research method used the case study method (Case Study) by applying quantitative methods. The data used is secondary data from the Directorate General of Plantations, BPS, and UN Comtrade, namely data on tea exports, tea imports, total export value, total world export value for tea, and total world export value. The analysis used is RCA (Revealed Comparative Advantage) Analysis and Trading Specialization Index (TSI).  The research results show that Indonesia's RCA value is between 1.24 – 1.74, so it can be concluded that Indonesia has comparative competitiveness. However, when compared with other countries, Indonesia is in third place, after India and China. The average TSI for Indonesia was 0.56 in the five years (2016 - 2020), which shows Indonesia's position as a tea-exporting country and is at a growth stage.